2001
DOI: 10.1006/jbin.2001.1028
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety, Potential Adverse Drug Events, and Medical Device Design: A Human Factors Engineering Approach

Abstract: Adverse drug events are the single leading threat to patient safety. Human factors engineering has been repeatedly proposed, but largely untested, as the key to improving patient safety. The value of this approach was investigated in the context of a commercially available patient-controlled analgesia device that has been linked with several alleged patient injuries and deaths. Several reports have stated that errors in programming drug concentration were made during these adverse drug events. A simulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 12 publications
1
96
0
4
Order By: Relevance
“…22,23 As shown in the Table, this case demonstrated six of 17 potential errors associated with the PCA pump. While there was no actual transfer of patient care, the settings were not appropriately reviewed at the time of initiation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…22,23 As shown in the Table, this case demonstrated six of 17 potential errors associated with the PCA pump. While there was no actual transfer of patient care, the settings were not appropriately reviewed at the time of initiation.…”
Section: Discussionmentioning
confidence: 87%
“…Although the machine has a "four-hour limit", the incorrect programming in this case would negate this limit check on the machine since the machine would assume the 30 mL syringe contained only 15 mg of morphine, instead of the contained drug mass of 150 mg. A human factors engineering approach to designing the programming interface has been shown to reduce programming errors. 22 In addition, the implementation of bar code technology promises to further reduce the risk of programming errors. 24 Neither of the two nurses involved in the initial programming was familiar with the programming of these pumps.…”
Section: Discussionmentioning
confidence: 99%
“…The commonality in these cases is important; recent laboratory research shows that redesigning the programming interface for this particular device may virtually eliminate concentration programming errors. 20 It is well known that voluntary and mandatory reporting systems for adverse events and ADE, including the FDA MDR database, suffer from severe underreporting; epidemiological studies revealed reporting rates that ranged from a low of 1.2% to a high of 7.7%. 2, [21][22][23] We used these extreme values to transform the minimum and maximum reported frequencies in Table I into evidence-based high and low estimates of the true incidence of patient mortality associated with programming errors with this device.…”
Section: éLéments Cliniquesmentioning
confidence: 99%
“…First and foremost, user interfaces for PCA pumps should be redesigned to make them easier to program based on human factors engineering techniques. 20 Second, caregivers should always report any difficulty, near miss, injury, or death associated with PCA pumps and other medical devices using Health Canada's Medical Devices Problem Report Form so that the true magnitude of the problem can be established. The required form is easy to fill out and can be found on the internet (www.hc-sc.gc.ca/hpfb/inspectorate/md_pro_rep_form_tc_e.html).…”
Section: éLéments Cliniquesmentioning
confidence: 99%
“…[2][3][4] [3] False triggering, for example, due to a short circuit in the PCA button 5 or for other reasons. 6,7 [4] False triggering by proxy (e.g., relatives pushing the PCA button because Granny is too sleepy to do it herself).…”
mentioning
confidence: 99%